Expression of neuroepithelial transforming gene 1 is enhanced in oesophageal cancer and mediates an invasive tumour cell phenotype. - PIDGEON, GRAHAM (My University, 2013)
Introduction Neuroepithelial Transforming Gene 1 (NET1) is a well characterised oncoprotein and a proven marker of an aggressive phenotype in a number of cancers, including gastric adenocarcinoma. We aimed to investigate whether NET1 plays a functional role in oesophageal cancer (OAC) and its pre-malignant phenotype Barrett’s oesophagus. Methods Baseline NET1 mRNA levels were determined by qPCR across a panel of six cell lines, including normal oesophageal, Barrett’s and OAC derived cells. Quantification of NET1 protein in OAC cells was performed using Western blot and immunofluorescence. NET1 expression was modulated by treating with lysophosphatidic acid (LPA) and NET1-specific siRNA. The functional effects of NET1 knockdown were assessed in vitro using proliferation, migration and invasion assays. Results NET1 expression was increased in Barrett’s and in OAC-derived cells in comparison to normal oesophageal cells. The highest expression was observed in OE33 a Barrett’s-related OAC cell line. NET1 protein and mRNA expression was enhanced by LPA treatment in OAC and furthermore LPA treatment caused increased proliferation, migration and invasion in a NET1-dependent manner. NET1 knockdown resulted in reduced OAC cell proliferation and invasion. Conclusions As found in other malignancies, NET1 expression is elevated in OAC and its pre-malignant phenotype, Barrett’s oesophagus. NET1 promotes OAC cell invasion and proliferation and it mediates LPA-induced OAC cell migration.
PUBLISHED
Keywords: Gastrointestinal oncology; Guanine nucleotide exchange factor; Oesophageal cancer; NET1; Neuroepithelial transforming gene 1